Strategi Pengembangan Ekonomi Kreatif di Kampung Tenun Ikat Berbasis Community Development - Meylin Azza Nabila, Putri; Soseco, Thomas (Politeknik Baubau, 2025)
Bandar Kidul Ikat Weaving Tourism Village in Kediri is one of the areas with quality traditional weaving products that have high cultural value in Kediri. Although Pokdarwis has been formed to develop tourism, there are still challenges. This study aims to analyze the implementation of strategies by Pokdarwis and design a new strategy based on community development to increase the income of local communities. The research approach used mixed methods with SWOT analysis to identify internal and external conditions, and QSPM to determine priority strategies. The results showed that the current strategy implemented by Pokdarwis as the tourism manager is still not optimal due to obstacles. The SWOT analysis identified that the main strengths of Bandar Kidul Ikat Weaving Tourism are high product quality and unique motifs. However, weaknesses such as limited capital, less effective marketing, and lack of artisan regeneration pose significant challenges. The QSPM results state that, the main recommended strategy is one of the WO (weakness-opportunity) strategies with the highest TAS (Total Attractiveness) score of 8.645. The strategy involves and collaborates with several parties to increase public awareness of the value of weaving art, improve promoting ikat weaving, and expand the market.